Effects of continuous and intermittent cadmium exposure on HPGL axis, GH/IGF axis and circadian rhythm signaling and their consequences on reproduction in female zebrafish: Biomarkers independent of exposure regimes. (November 2021) - Zheng, Jia-Lang; Peng, Li-Bin; Xia, Li-Ping; Li, Jiji; Zhu, Qing-Ling
Abstract: Typical biomarkers of cadmium (Cd) pollution have well been confirmed in fish from continuous exposure pattern. However, in a natural environment, fish may be exposed to Cd intermittently. In this study, juvenile female zebrafish were exposed for 48 days to 10 μg/L Cd continuously, 20 μg/L for 1 day in every 2 days or 30 μg/L for 1 day in every 3 days. The toxic effects were evaluated using 8 various physiological and biochemical endpoints like specific growth rate (SGR), 17β-estradiol (E2) and vitellogenin (VTG) concentrations in plasma, reproductive parameters (gonadosomatic index (GSI), egg-laying amount, spawning percentage, and hatching and mortality rate of embryos). Transcription of 59 genes related to hypothalamic-pituitary-gonadal-liver (HPGL) axis, circadian rhythm signaling and insulin-like growth factor (IGF) system was examined. SGR, spawning percentage, E2 and VTG levels declined in fish exposed to 10 and 20 μg/L Cd but remained relatively stable in fish exposed to 30 μg/L Cd. Exposure to 10, 20 and 30 μg/L Cd significantly reduced GSI, hatching rate and mortality rate. Similarly, mRNA expression of 27 genes were sensitive to both continuous and intermittent Cd exposure. Among these genes, expression levels of 10 genes had more than 5-fold increase or decrease, including mRNA levels of vtg1, vtg2, vtg3, esr1, igf2a, igf2b, igfbp5b, nr1d1, gnrh3 and gnrhr4 . The most sensitive molecular biomarker was vtg3 expression with 1500–3100 fold increase in the liver. The present study, for the first time, provides effective candidate biomarkers for Cd, which are independent of exposure regimes. Highlights: Biomarkers of continuous and intermittent Cd exposure were investigated. HPGL axis, GH/IGF axis, circadian rhythm signaling, growth and reproductive capacity were examined. Expression of 27 genes and 3 biochemical indicators were responsive to both exposure regimes. Mortality of offspring was the most sensitive physiological biomarker. The priority molecular biomarkers were mRNA levels of vtg1, vtg2, vtg3 and esr1.